ASPEK HUKUM JUAL BELI MINUMAN BERALKOHOL BERPENGARUH DALAM MOBILITAS TRANPORTASI MASYARAKAT DI KOTA PONTIANAK - NIM. A1012211043, HERI KURDIANTO (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Traffic accidents are one of the negative impacts of traffic growth, in addition to congestion, air pollution, and noise. Based on data from the West Kalimantan Regional Police Traffic Unit, especially the Pontianak City Police Traffic Unit regarding traffic accident cases, the number of traffic accidents (Laka Lantas) in West Kalimantan throughout 2021 reached hundreds. In a press conference at the end of 2021, the West Kalimantan Police explained the number of Laka Lantas cases they had handled throughout that year. The author is interested in expressing scientific writing with the title